PATTERN OF HOMICIDAL DEATHS IN NORTH EAST DELHI AND NCR (Journal of Forensic Medicine & Toxicology, 2018)
A systematic review of homicidal cases was undertaken in the department of Forensic Medicine at the Guru Teg Bahadur hospital and UCMS, Delhi, to find out trends in homicides. The present study comprises of 85 victims of homicide in North-East Delhi and the surrounding areas of Ghaziabad, whose postmortem examination was conducted at the hospital. The commonest age group of the victims was 21-30 years (38.8%), followed by 31-40 years with 21 cases (24.7%). Males were victimized approximately 5 times more than females. Chest was the most common region sustaining fatal injury leading to death in 30 cases (35.29%). The most common mode of homicide was stabbing/cutting with a total number of 38 cases (43.7%), followed by blunt force with 20 cases (23.0%). The cause of death was found to be haemorrhage and shock in 62 cases (72.94%) followed by Head Injury seen in 16 cases (18.82%).
Keywords: Homicidal deaths; Survival period; Gunshot; Blunt & Sharp force